Association of SERPIND1 expression with grade, stage and presence of metastasis in breast cancer (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
The role of SERPIND1 gene in the development of breast cancer is completely unknown. The aim of the present study was to assess the expression of SERPIND1 in patients suffering from breast malignancies. Tumoural specimens and non-tumoural adjacent tissues were collected from 31 patients who were pathologically confirmed for breast cancer. Furthermore, 43 fasting venous blood samples were collected from the breast cancer patients as well as from the healthy volunteers as control group. The SERPIND1 mRNA expression levels were assessed using the q-RT PCR while the plasma levels of SERPIND1 protein were detected using ELISA. The SERPIND1 relative expression levels were compared with the clinicopathological factors. The expression of the SERPIND1 was significantly higher at both mRNA and protein levels in breast cancer patients compared to the control groups. Moreover, the relative expression of the SERPIND1 showed a significant positive correlation with cancer grade, stage and presence of metastasis (P< 0.05). The findings suggest that the SERPIND1 may be a metastasis-enhancer factor in breast cancer and a strong predictive marker for distinguishing patients with poor prognosis.